RISKS IN THE INVESTMENT AND FINANCING IN REAL ESTATE - Ekaterina Yu. Kalashnikova (Вестник Северо-Кавказского федерального университета)
In this article the importance given to the analysis and evaluation of the risks of investing in real estate and financing, and provides recommendations to reduce them in various ways that an investor can choose without compromising yourself.